The influence of cations on the dipole moments of neighboring polar molecules. Issue 8 (29th June 2021) - Bakó, Imre; Csókás, Dániel; Mayer, István; Pothoczki, Szilvia; Pusztai, László
Abstract: In this article we show how the dipole moment of a single molecule in a cluster can be calculated and used for describing the polarization effect. Additionally, we review the accuracy of the calculation of the dipole moment of several simple protic and aprotic molecules. It is shown that the dipole moment of polar (water, methanol, formamide, acetone and acetonitrile) molecules in the neighborhood of a cation is increased primarily by polarization from the bare electrostatic charge of the cation, although the effective value of the latter is somewhat reduced by "back donation" of electrons from neighboring polar molecules. In other words, the classical picture may be viewed as if a point charge slightly smaller than the nominal charge of the cation would be placed at the cation site. It was found that the geometrical arrangement of the polar molecules in the first solvation shell is such that their mutual polarization reduces the dipole moments of individual molecules, so that in some cases they become smaller than the dipole moment of the free protic or aprotic molecule. We conjecture, for the first time, that this behavior, namely the about 10%–20% decrease of the dipole moment of water in the first shell of cations, with the cation itself removed, is essentially a manifestation of the Le Chatelier–Braun principle. We also remark that if the cation‐molecule bond order is too large then the calculated dipole moment for these complexes can be questionable, due to the questionable definition of a single molecule within the "supermolecule"‐like cluster. Abstract : We conjecture, for the first time, that this behaviour, namely the about10‐20% decrease of the dipole moment of water in the first shell ofcations, with the cation itself removed, is essentially a manifestation of the Le Chatelier–Braun principle.